Imprensa, ditadura e abertura política: entre consentimentos, atritos e ambivalências - a atuação dos jornais cearenses Correio da Semana e O Povo (1974-1985) - Silva, João Batista Teófilo (2015)
This work tries to understand the actions of Ceará's newspapers Correio da Semana and O Povo within the fight for redemocratization conjuncture between 1974 and 1985. It also tries to understand the role played by these newspapers in the consolidation of the opening process "slow, gradual and safe". It faces the role of the press as a social practice and an ingredient for historical events, allowing us to understand the role that the press plays in the formation of memories, in building consensus and in the struggles for hegemony, establishing alliances with political forces in various situations. This is not about understanding the actions of these newspapers from mere speeches, as if these were not part of the events that sought to intervene in the social. But it is about understanding these actions as a social constitutive language that tries to defend social projects, articulate political pacts and indicate perspectives from the past, present and future. The studies on the performance of the Brazilian press during the civil-military dictatorship, centralized in newspapers from the states of Rio de Janeiro and São Paulo, often tend to simplify the historical process from the actions of few newspapers, homogenizing issues that are way more complex. The reflections of this research try to provide new contributions to the generalized views, that reduce the role of the Brazilian press to a few newspapers which, despite their importance, are far from representing a historical experience that is more complex. Reflecting about the consents, friction and ambivalences that permeate the work of these newspapers, this research seeks to show that it has not been always that the Brazilian press has nurtured supportive relationships with the dictatorship to then move to the opposition field. The supportive relationships also marked by friction, not sum up in comfortable dichotomies as in favor and against. Such relationships, more complex, lead us to thinking on the role the press played in consolidating the dictatorship and in building its political opening process as revealed within the many facets of the dictatorial project, which was not simply imposed on March 31, 1964, but built from the military alliances with civilian sectors of society, including the newspapers Correio da Semana and O Povo